Identification of Active Compounds of Annona muricata (Soursop) Leaf Wax Extract Using GC-MS - , Fai F. Yirankinyuki, Buhari Magaji, Wilson L. Danbature, Abdullah M. Abdullah (Archives of Current Research International, 2020)
Soursop plant (Annona muricata L.), is widely used for both industrial and medicinal applications. In view of this, the present study aims at extraction and characterization of soursop leaf wax using gas chromatography-mass spectrometry (GC-MS). The results of the GC-MS analysis of soursop wax show the presence of 26 different compounds. From the results, it could be concluded that A. muricata contains various compounds that could be useful in different industries. Thus, soursop wax could be a good alternative source for many industrial chemicals that are currently sourced from petroleum which is non-renewable.